Determination of the odour adsorption behaviour of wool - Yilmaz, Ebru (Array, 2020)
In this study, the adsorption/desorption behaviours of water vapor on wool, as well as of the redolents, such as acetic acid and benzaldehyde, have been investigated. For this purpose, static and dynamic experiments were carried out. Static experiments were conducted to model stagnant environments. In the experiments, wool came into contact with the material to be adsorbed or dry air and the weight increase/decrease was recorded for a certain period of time. The results obtained showed that the wool adsorbed the benzaldehyde very little, whereas the adsorbed amount and the rate were abundantly increased for acetic acid under the same conditions. From these findings, the adsorption capacity of wool for the redolents was tentatively ranked in accordance with their adsorbed amounts as acetic acid>water>benzaldehyde.